DETERMINAN CASH HOLDING PERUSAHAAN CONSUMER NON-CYCLICALS - Oktafiani, Regina; Surjadi, Lukman (Jurnal Paradigma Akuntansi, 2025)
The purpose of this study is to obtain empirical evidence about the effect of profitability, liquidity, firm size, leverage, and capital expenditure on cash holding in consumer non-cyclicals companies listed on the Indonesia Stock Exchange in 2018-2021. The sample in this study were 33 consumer non-cyclicals companies selected using purposive sampling method. Data processing in this study used SPSS 26 software. The results of this study indicate that profitabilty dan liquidity have am effect on cash holding, while firm size, leverage, dan capital expenditure have no effect on cash holding. The implication of this study is that cash holding plays an important role for the company because it is used as a source of funding and as a liquid asset to support the company's necessity.